The extent of using computers in developing the learning independence of students with learning difficulties from the viewpoint of their teachers - Almughira, Maram Saud (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the uses of computers to increase the independence of students with learning difficulties in the primary stage from the point of view of female learning difficulties teachers, and the study adopted the descriptive-analytical approach, and a random sample of 70 female teachers of learning difficulties was selected randomly from elementary schools for girls. In the city of Riyadh, their data were collected through a questionnaire. The study showed a high level of support by female teachers of learning difficulties for the importance of using the computer in increasing the independence of students with learning difficulties to learn, there were not of statistically significant differences in their attitudes according to the educational qualification, while the differences were statistically significant according to years of experience. The study recommended working on everything that enhances the use of computers to increase the independence of female students with learning difficulties in the primary stage, including awareness and training courses.
Keywords: Computer; Learning Disabilities; Riyadh